The Pluralist Argument of The Sufis: A Study of Al-Qusyairi's Interpretation Of The Verse Of Jihad - Moh. Badrus Sholeh (Studi Multidisipliner: Jurnal Kajian Keislaman, 2023)
One of the figures who has a pluralist view is Al-Qusyairi. Because he has a different interpretation of the verse jihad, which has been used as a pretext by perpetrators of terrorism and radicalism to commit violence by interpreting it literally and textually by denying other meanings. The formulation of the problem posed is how Al-Qusyairi interprets the verse of jihad and its implications. This qualitative research combines library research on interpreting Al-Qusyairi, lathaif al-Isyarah. This paper finds that Al-Qusyairi's interpretation of jihadist verses uses a Sufistic interpretation model. So, the meaning of jihad or war in the Qur'an refers to internal believers of religions, not external followers of other religions. On the other hand, this paper also finds that the interpretation of Al-Qusyairi departs from the assumption that followers of other religions have the same opportunity to gain the pleasure of Allah SWT on condition of faith in Him and the last day.